2015
DOI: 10.1167/iovs.14-15004
|View full text |Cite
|
Sign up to set email alerts
|

Small Fiber Peripheral Neuropathy in Wilson Disease: An In Vivo Documentation by Corneal Confocal Microscopy

Abstract: The CCM showed significant corneal changes in SBNP, with concomitant corneal epithelium changes in WD, demonstrating the presence of small fiber peripheral neuropathy in these patients. The CCM may contribute to diagnosis and monitoring of the peripheral nervous system involvement in WD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…Initial reports described predominant demyelinating involvement, whereas subsequent reports focused on axonal impairment. 1 We also recently reported small fiber neuropathy mostly correlating with somatic rather than autonomic small fibers in WD patients. 4 Our patients had normal nerve conduction studies, but half of them had abnormal skin wrinkling test that, similar to corneal confocal microscopy, also strongly correlated with abnormalities on intraepidermal nerve fiber density.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…Initial reports described predominant demyelinating involvement, whereas subsequent reports focused on axonal impairment. 1 We also recently reported small fiber neuropathy mostly correlating with somatic rather than autonomic small fibers in WD patients. 4 Our patients had normal nerve conduction studies, but half of them had abnormal skin wrinkling test that, similar to corneal confocal microscopy, also strongly correlated with abnormalities on intraepidermal nerve fiber density.…”
mentioning
confidence: 71%
“…We read with interest the article written by Sturniolo and colleagues 1 and recently published in Investigative Ophthalmology and Visual Science. The authors evaluated 24 patients with Wilson disease (WD) and 24 controls by corneal confocal microscopy and reported that patients with WD exhibited significantly altered corneal subbasal nerve plexus (reduced number of fibers, number of branchings and beadings, as well as reduced nerve fiber length density, with associated increased fiber tortuosity).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Both manifestations may resolve with continued therapy [39] . Small fiber peripheral neuro pathy involving the corneal nerve plexus [40] , as well as neuronal degeneration involving the retina have also been described [41] , using novel techniques such as corneal confocal microscopy and spectral domain optical coherence tomography, respectively. Psychiatric abnormalities, which may be present before hepatic or neurological signs in up to one third of patients [42] , include decreased academic performance or personality changes, sexual exhibitionism, impulsiveness, labile mood, inappropriate behavior, depression, paranoia, and schizophrenia, leading also to suicide in a discrete number of cases [15,33,43,44] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%